Persepsi Penyuluh Pertanian terhadap Cyber Extension (Suatu Kasus pada Penyuluh Pertanian di Kabupaten Bandung Barat) - Rosadi, Osad Imron; Hapsari, Hepi; Trimo, Lucyana (Universitas Galuh, 2025)
Mastery of various information system technologies in agriculture will greatly support the competence of agricultural extension workers. Extension workers must have competence before conducting counselling, education and training for farmers so that they can strengthen farmers' perceptions of technological innovation. This study aims to: (1) Analyse the level of implementation of cyber extension in West Bandung Regency, (2) Analyse the perception of agricultural extension workers towards cyber extension in West Bandung Regency, (3) Analyse the personal characteristics, motivation and independence of agricultural extension workers in West Bandung Regency, and (4) Analyse the partial and simultaneous effects of personal characteristics, motivation, and independence of agricultural extension workers on the perception of agricultural extension workers towards cyber extension in West Bandung Regency. The research method used is the survey research method. The analytical tool used is multiple linear regression analysis. The results showed that, (1) The level of application of cyber extension in West Bandung Regency was classified as good. Agricultural extension workers often use cyber extension to support their extension activities. (2) Perceptions of agricultural extension workers in West Bandung Regency assess the existence of cyber extension as having an important role in assisting extension activities. (3) The main motivation of agricultural extension workers in West Bandung Regency is to excel. Then the independence of extension workers can be said to be good, both emotionally, intellectually, economically, and socially. (4) Personal characteristics, motivation, and independence of extension agents have a significant influence simultaneously on the perception of agricultural extension agents in West Bandung Regency regarding cyber extension. Partially personal characteristics do not have a significant influence on the perception of agricultural extension workers in West Bandung Regency regarding cyber extension. While the motivation and independence of extension workers partially have a significant influence on the perceptions of agricultural extension workers in West Bandung Regency regarding cyber extension.